2021
DOI: 10.1109/jsen.2021.3085128
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-Printed, Nanofiber-Based Soft Capacitive Pressure Sensors for Tactile Sensing

Abstract: The development of soft electronics is critical to the realization of artificial intelligence that comes into direct contact with humans, such as wearable devices, and robotics. Furthermore, rapid prototyping and inexpensive processes are essential for the development of these applications. We demonstrate here an additive, low-cost method for fabricating polydimethylsiloxane based soft electronics by inkjet printing. Herein, a novel approach using a water-soluble polyvinyl alcohol layer as the substrate, inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…have demonstrated using inkjet printing to fabricate soft capacitive pressure sensors for tactile sensing using PDMS as the dielectric layer and silver nanoparticle ink for the conductive electrodes. [ 222 ] On the other hand, Faller et al. fabricated an integrated capacitive multimodal sensor using hybrid 3D printing technology that combines 3D printing and inkjet printing for the fabrication of a robotic gripper.…”
Section: Design and Fabrication Of Soft Sensors For Soft Grippermentioning
confidence: 99%
See 1 more Smart Citation
“…have demonstrated using inkjet printing to fabricate soft capacitive pressure sensors for tactile sensing using PDMS as the dielectric layer and silver nanoparticle ink for the conductive electrodes. [ 222 ] On the other hand, Faller et al. fabricated an integrated capacitive multimodal sensor using hybrid 3D printing technology that combines 3D printing and inkjet printing for the fabrication of a robotic gripper.…”
Section: Design and Fabrication Of Soft Sensors For Soft Grippermentioning
confidence: 99%
“…For instance, Mikkonen et al have demonstrated using inkjet printing to fabricate soft capacitive pressure sensors for tactile sensing using PDMS as the dielectric layer and silver nanoparticle ink for the conductive electrodes. [222] On the other hand, Faller et al fabricated an integrated capacitive multimodal sensor using hybrid 3D printing technology that combines 3D printing and inkjet printing for the fabrication of a robotic gripper. [223] Interestingly, inkjet printing has been used for the coating of the passivation layer for smoothening of the surface of 3D printed structure to facilitate subsequent printing of electronics on the surface.…”
Section: Material-jetting Techniquesmentioning
confidence: 99%
“…Inkjet printing technologies have been widely used for the development of flexible electronics as they offer a fabrication alternative to lithography-based approaches [ 68 , 98 ], introduce the use of new intrinsically stretchable inks [ 39 , 97 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ], and avoid the challenges related to the brittleness of traditional materials used to manufacture tactile sensors [ 7 , 82 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ,…”
Section: Inkjet Printing Technologymentioning
confidence: 99%
“…Basak et al [ 136 ] and Zhang et al [ 152 ] developed their printed capacitive sensors on thermoplastic polyurethane (TPU) and aluminium substrates, respectively. Mikkonen et al [ 140 ] proposed a novel approach using a water-soluble polyvinyl alcohol (PVA) layer as the substrate.…”
Section: Inkjet Printed Tactile Sensorsmentioning
confidence: 99%
See 1 more Smart Citation